N-Legendre and N-slant curves in the unit tangent bundle of surfaces - Hathout, Fouzi; Bekar, Murat; Yayli, Yusuf (Kuwait Journal of Science, 2017)
Let (T1M; g1) be a unit tangent bundle of some surface (M; g) en-dowed with the induced Sasaki metric. In this present paper, we de- ne two kinds of curves called N-legendre and N-slant curves as curveshaving an inner product of normal vector and Reeb vector zero andnonzero constant respectively and several important characterizationsof these curves are obtained.